Development and Performance Evaluation of a Semi-Automatic Pineapple Peeling Machine - ABDUL VAHID P ANJALI A.V ANJITHA P.K ARUN KRISHNAN A NETHU K.P; Dr. Santhi Mary Mathew (Guide) (Tavanur 2017 Department of Food and Agricultural Process Engineering)
Development and Performance Evaluation of a Semi-Automatic Pineapple Peeling Machine
Development and Performance Evaluation of a Semi-Automatic Pineapple Peeling Machine